OP10 Approaches To Gain Reimbursement For Medical Devices In Germany - Neeser, Kurt; Müller, Elvira; Oelze, Ilse-Barbara (International journal of technology assessment in health care, 2019)
Copyright © Cambridge University Press 20192019Cambridge University PressIntroductionMedical devices (MDs) differ regarding their risk class (I to III), operational area (in-, outpatient), intended use (diagnostic, monitoring, intervention), and with regard to available clinical evidence. Therefore, the market access processes as well as the approach of gaining reimbursement differ significantly. From a variety of potential approaches the underlying analysis illustrates five MD-specific processes.MethodsBased on a systematic search of publicly available regulations the main pathways of potential reimbursement for MDs were evaluated.ResultsMDs to be used in the in-patient setting can be divided into three categories: an innovative MD (a) is exceeding a current reimbursement framework (German Operations and Procedures Key (OPS) / diagnosis related groups (DRG)), (b) falls within an existing reimbursement rate, or (c) the MD is based on a known mode of action (MoA) for which already adequate reimbursement exists. Due to less empirical data from MDs for a) and b), a health technology assessment (HTA) is required before inclusion in a DRG, whereas a MD with known concept (c) will be grouped into existing price structures. Initiators of these processes are hospitals through a so-called NUB application. MDs entering the outpatient sector are covered by another reimbursement catalogue (EBM/GOÄ) and have to pass an assessment by the G-BA (rapid HTA) if based on new MoA (d). Such an assessment can only be initiated by respective umbrella organizations of service providers (e.g. KBV (National Association of Statutory Health Insurance Physicians)). MDs not being positively recommended by the G-BA are not reimbursable. For MDs (e) with known MoA no HTA is required.ConclusionsFor a successful market launch including sufficient reimbursement not only the market potential, but also the specific regulatory pathways have to be considered carefully. New and innovative MDs in the outpatient sector may have a longer application process to gain a positive reimbursement decision than MDs used in inpatient setting.